Optimization of torpedo scad fish (Megalaspis cordyla) viscera protease extraction and purification / Normah, I. and Nor Aryan Nabila, N.A. - I., Normah; N.A, Nor Aryan Nabila (Faculty of Applied Sciences, 2019)
Protease comprises the class of enzymes that are most used worldwide, accounting for 60% of the world total enzyme production. This study was carried out to determine the proteolytic activity of protease extracted from torpedo scad fish (Megalaspis cordyla) viscera, and to determine the optimum pH and ammonium sulphate concentration for the extraction and purification of the extracted visceral protease. The combination of optimum condition for pH and ammonium sulphate concentration was optimized using the Response Surface Methodology (RSM). The crude enzyme extracts are then precipitated in ammonium sulphate followed by dialysis and gel filtration chromatography where the proteolytic activity was studied. The concentration of ammonium sulphate used ranged from 40-80% and pH used for extraction was between 6-9. The enzyme showed the highest proteolytic activity at pH 9 and 80% ammonium sulphate concentration matching with RSM suggested condition. The proteolytic activity obtained under this condition was 445U. The total activity of the crude extract, ammonium sulphate precipitation, and dialyzed proteases were 820, 680 and 425U, respectively. The viscera contained 15.87% protein. Thus, the optimum condition for extraction and purification of protease from torpedo scad fish viscera were at pH 9 with 80% ammonium sulphate concentration, respectively resulting in high proteolytic activity.